Dissecting COVID-19 Pandenomics: A New Management Discourse - Sthapit, Arhan (Journal of Business and Social Sciences Research, 2020)
With the novel coronavirus outbreak adversely affecting economies all over the world and putting the humankind in probably the most difficult time in modern history, an imperative need to understand, analyse and dissect the very economics of pandemic—or the ‘Pandenomics’ of COVID-19— has been felt. In our human lives and politico-economic spheres, much has either changed or metamorphosed after the virus outbreak, as the world moves towards the end of 2020. The world has made transition from physical to virtual and digital. Globalisation has witnessed deceleration in its pace, if not reversal. We managers should well analyse and dissect the COVID pandenomics to draw its telling lessons for managing economies and organisations in both short and long terms. We can successfully convert the volatility, uncertainty, complexity, and ambiguity (or, VUCA-1), into Vision, Understanding, Clarity and Agility, or VUCA-2 for which the management leaders should possess and develop the essential competency to ‘lead through influence.’